Analysis of Errors in Using Punctuation and Writing in Indonesian in Physics Learning Modules in Middle Schools: Case Study in Semarang City - Harahap, Safinatul Hasanah; Syahputri, Airi Rizki; Hura, Dania Priskilla; Simanihuruk, Rahel Novita (CV. Rayyan Dwi Bharata, 2024)
This research aims to investigate common errors in the use of punctuation and writing in Indonesian in physics learning modules at secondary school level in Semarang City. These errors can interfere with students' understanding of the material presented in the module. Therefore, it is necessary to improve and perfect the use of Indonesian punctuation and writing in physics learning modules in order to improve the quality and effectiveness of learning. By analyzing these errors, this study hopes to provide better insight into linguistic aspects in physics learning, and provide recommendations for improvements to improve the quality of learning materials. Analysis methods include collecting learning modules, identifying errors, classifying types of errors, analyzing the causes of errors, and recommending improvements. It is hoped that the results of this study can make a significant contribution to the development of the education curriculum in Indonesia.